2018
DOI: 10.36222/ejt.481221
|View full text |Cite
|
Sign up to set email alerts
|

Mechanical Properties of the Composite Material Produced by the Mixture of Expanded Perlite, Waste Marble Dust and Tragacanth

Abstract: In this study, the strength characteristics of the expanded perlite aggregate, waste marble dust and tragacanth added cement based composite material were investigated. A composite construction material was prepared using expanded perlite aggregate with a particle size of 0-2 mm and 2-4 mm at the ratio of 10%, 30% and 50% by weight, waste marble powder produced by sieving through 0.25 mm sieve at the ratio of 10% and 20%, tragacanth at the ratio of 0%, 0.5% and %1 and CEMI 42.5 N type Portland cement. Density,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
3
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 6 publications
0
3
0
Order By: Relevance
“…Researchers have attempted to use marble waste particulates in paver blocks [ 19 ], soil stabilization [ 11 , 20 ], cement-based adhesive mortar [ 21 ], and as a replacement of conventional natural aggregates in concrete [ 4 , 8 , 22 , 23 , 24 , 25 ]. Attempts have also been made to use marble waste for manufacturing cementitious roofing tiles [ 26 ], preparing polymer concrete with unsaturated pre-accelerated polyester resin [ 27 ], a cement-based composite material with expanded perlite and tragacanth (plant resin) [ 28 ], composite bricks [ 2 , 6 , 29 ], artificial stones, unsaturated polyester resin, and epoxy resin as binders [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have attempted to use marble waste particulates in paver blocks [ 19 ], soil stabilization [ 11 , 20 ], cement-based adhesive mortar [ 21 ], and as a replacement of conventional natural aggregates in concrete [ 4 , 8 , 22 , 23 , 24 , 25 ]. Attempts have also been made to use marble waste for manufacturing cementitious roofing tiles [ 26 ], preparing polymer concrete with unsaturated pre-accelerated polyester resin [ 27 ], a cement-based composite material with expanded perlite and tragacanth (plant resin) [ 28 ], composite bricks [ 2 , 6 , 29 ], artificial stones, unsaturated polyester resin, and epoxy resin as binders [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%
“…Researchers have being attempting to utilize marble waste in pavement blocks [57], stabilization of soil [58,59], cement mortar [60] and in cement concrete [9,61,62]. Attempts are being done for using marble waste in making roofing tiles [63], polymer concrete with polyester resin [64], cement-based composites with tragacanth (plant resin) and expanded perlite [65], bricks [7,66,67], artificial stones with epoxy and polyester resins [68,69]. Gulden Cagin Ulubeyli et al have reported that the use of waste marble in the conventional or self-compacting concrete mix as an admixture material or aggregate is suitable as it can improve durability properties of the concrete.…”
Section: State Of the Artmentioning
confidence: 99%
“…[8]. The quality of the brick is highly dependent on the properties and composition of the raw materials, the production procedure, the firing method, and the temperature and time [9][10][11] The sintering process in clay bricks increases the strength of bricks. Sintering is the binding mechanism of clay particles and it can only be achieved under the influence of heat [12].…”
Section: Introductionmentioning
confidence: 99%